Bentuk, Makna dan Fungsi Aksara Bilangan dalam Penaggalan Kalender Hatuhaha di Pelauw Maluku (Kajian Semiotika) - Susi Hardila Latuconsina (Kantor Bahasa Provinsi Maluku, 2022)
The diversity of calendar characters in the Indonesian Muslim community is very close to the entry of Islam to the archipelago. This assumption is clearly based on the condition in which the community is still very strong in maintaining the customs and traditions related to the religious and Sufistic patterns of the tarekat. The problem being studied is how the form, meaning and function of the calendar calendar used in religious traditions in Pelauw. The purpose of this research is to describe the form, meaning, and function of the calendar calendar in Pelauw. Data collection techniques include observation, interviews, field notes and documentation. Based on the research results it was found that the Takwin Jum'atiyah number used Hisab Urfi. The first year in the Hijriyah Hatuhaha calendar is the year Alif 1 where 1 Muharram falls on a Friday so it is called Bilangan Jum'atiyah. Implementation of the Calendar Calendar related to religious traditions and rituals in Pelauw, the Ma'atenu [cakalel dance, Aroha [celebration of the birthday of the Prophet Muhammad SAW, and Ma'amara Tenuno.